Greenland, landscape of Renbukten, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig 139 - Valley leading to Renbukten containing a small glacier from the northeast. Immediately to its left an ice-free valley enters from the northwest. (see Fig. 146) July 29, 1931. (X). (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp. 106). New York: American Geographical Society) Valley leading to Renbukten containing a small glacier from the northeast. July 29, 1931. From: Louise A. Boyd: Fiord Region of East Greenland, Fig. 139 Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society